Conservation agriculture conference and fieldtrip in Cambodia / Noor Azrimi Umor - Umor, Noor Azrimi (UiTM Cawangan Negeri Sembilan, 2022)
The Third International Sustainable Agricultural Intensification and Nutrition Conference (SAIN3) was held on June 27-28, 2022 at the Angkor Paradise Hotel in Siem Reap. The conference venue was very well organised and suitable for the event in the heart of Siem Reap city. The SAIN3 conference was jointly organised by CE SAIN – Royal University of Agriculture, Cambodia with support from various organisations such as Feed The Future, USAID, Kansas State University American Soybean Society (ASA), World initiative for soy in human health (WISHH) and Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA). Within two days, the conference was organised into a total of 6 sessions, including 6 general plenary presentations by 6 invited speakers, three parallel sessions and one poster presentation. The conference was attended by about 100 participants from eight countries. The aim of the conference was to provide a platform for researchers, students and professionals to learn about and discuss sustainable agricultural intensification and nutrition while addressing the importance of food security.